The chain mediating effect of empathy and communication ability on emotional intelligence and caring ability of nursing students - Yang, Yujie; Wang, Chang (Frontiers in Psychology, 2024)
Background The implementation of humanistic care is conducive to providing high quality nursing, improving patient satisfaction and establishing harmonious nursery-patient relationship. Current researchs show that humanistic caring ability is affected by emotional intelligence, empathy, interpersonal communication. But the exact relationship and internal mechanism of such factors have not been fully understood. Objective To explore the multiple mediating effect of empathy and communication ability on nursing students’ emotional intelligence and caring ability. Methods A case study was conducted by examining a sample of 1,165 nursing students from a junior college in Anhui, China. The multidimensional scales, and a self-designed demographic characteristics questionnaire were utilized. Path relationships and mutual effects were tested using structural equation modeling (SEM). Results Emotional intelligence, empathy, and communication ability were found to positively affect nursing students’ caring ability, as well as positive interrelationships with one another (standardized estimate = 0.312–0.584, p < 0.001). Communication ability and empathy play an important role in mediating the association between emotional intelligence and caring ability, and the effect sizes are 0.169 and 0.121, respectively, while the effect value of empathy and communication ability in emotional intelligence and caring ability was 0.034, which showed partial mediation of the association. The indirect effect of the structural equation was 77.14%. Conclusion The chain mediating role of empathy and communication ability in emotional intelligence and caring ability is explored, which not only enrichis previous studies, but also reveals the mechanism of emotional intelligence’s influence on caring ability. It is essential to continuously improve nursing students’ caring ability. From the perspective of nursing educators, they need to develop targeted approaches to help the nursing student improve their emotional intelligence, empathy, and communication skills, further enhancing their caring ability.